Alterações mamográficas em mulheres que vivem com HIV-aids - Mendes, Mônica Bannwart [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Background: Despite viral replication control, the chronic use of antiretroviral drugs leads to several changes in HIV carriers, among which are lipodystrophy and premature aging. The objectives were to evaluate mammographic density in women older than 35 years living with HIV/AIDS and relate breast density to age, time of exposure to antiretroviral therapy (cART), CD4 + T lymphocyte count, HIV viral load and the presence of lipodystrophy with incidence of breast fatty replacement (BFR). Methods: Observational cohort of women divided into two groups: G1, comprising 59 HIV-infected individuals and G2, consisting of 73 uninfected women, all aged 35 to 72 years. The following variables were studied: age at the moment of the interview, at menarche, at the last pregnancy and at menopause; use of hormones; breast pain; previous history of breast surgery and family history of breast or ovarian cancer. Results: BFR differences were observed between the groups when they were analyzed by age ranges, from 35 to 40 years (p=0.002) and from 41 to 45 years (p=0.041), with a higher proportion in G1 and in G2 at the age ranges of 51 to 55 years (p=0.046) and 56 to 60 years (p=0.005). The chance of lipodystrophy was 9.3- fold greater after 10 years of cART use, and it occurred in 29 (49.2%) women in G1. Conclusions: women with HIV/AIDS showed BFR at earlier ages when compared to uninfected women, and no relation to the number of pregnancies, lipodystrophy, having AIDS or asymptomatic infection or CD4 + T lymphocyte count was found

Apesar do controle da replicação viral, o uso crônico dos antirretrovirais leva a diversas alterações no portador de HIV, dentre elas, lipodistrofia e envelhecimento precoce. Os objetivos foram avaliar a densidade mamográfica de mulheres acima de 35 anos que vivem com HIV/aids, relacionando a densidade mamária à idade, tempo de exposição à terapia antirretroviral (cART), contagem de linfócitos T CD4+, carga viral do HIV e presença de lipodistrofia com incidência de lipossubstituição mamária (LM). Métodos: Coorte observacional de mulheres, dividida em dois grupos, G1 com 59 infectadas e G2 com 73 não infectadas pelo HIV, com idades de 35 a 72 anos. Foram estudados idades à entrevista, à menarca, à última gestação e à menopausa; uso de hormônios, dor mamária, histórias prévias de cirurgias de mama e familiar de câncer de mama ou de ovário. Resultados: Houve diferenças de LM entre os grupos, quando analisadas por faixas etárias, de 35 a 40 anos (p=0,002) e de 41 a 45 anos (p=0,041) com maior proporção em G1 e em G2, nas faixas de 51 a 55 anos (p=0,046) e 56 a 60 anos (p=0,005). A chance de lipodistrofia foi 9,3 vezes maior após 10 anos de uso de cART, ocorrendo em 29 (49,2%) mulheres de G1. Conclusões: mulheres portadoras de HIV/aids apresentam LM em idades mais precoces quando comparadas a mulheres não infectadas pelo vírus, não se encontrando relação com número de gestações, lipodistrofia, ter aids ou infecção assintomática e contagem de linfócitos T CD4+
Breast density assessment in womwn living with HIV/AIDS
Keywords: Mamas - Doenças; HIV (Vírus); AIDS (Doença); Densidade mamária; Agentes antirretrovirais; Breast - Diseases